Variability and performance evaluation of introgressed Nigerian dura x Deli dura oil palm progenies - Ahmad, Noh; Yusop, Mohd Rafii; Amiruddin, Mohd Din; Din, Ahmad Kushairi; Abdullah, Norziha; Rajanaidu, Nookiah; Abdul Malek, Mohammad (Fundacao de Pesquisas Cientificas de Ribeirao Preto, 2014)
Twelve introgressed oil palm (Elaeis guineensis) progenies of Nigerian dura x Deli dura were evaluated for bunch yield, yield attributes, bunch quality components and vegetative characters at the Malaysian Palm Oil Board Research Station, in Keratong, Pahang, Malaysia. Analysis of variance revealed significant to highly significant genotypic differences, indicating sufficient genetic variability among the progenies for bunch yield and its attributes, vegetative characters and bunch quality components, except fruit to bunch ratio. Fresh fruit bunch yield ranged from 167 kg·palm(-1)·year(-1) in PK1330 to 212 kg·palm(-1)·year(-1) in PK1351, with a mean yield of 192 kg·palm(-1)·year(-1). Among the progeny, PK1313 had the highest oil to bunch ratio (19.36%), due to its high mesocarp to fruit ratio, fruit to bunch ratio and low shell to fruit ratio. Among the progenies, PK1313 produced the highest oil yield of 31.4 kg·palm(-1)·year(-1), due to a high mesocarp to fruit ratio (61.2%) and a low shell to fruit ratio (30.7%), coupled with high fruit to bunch ratio (65.6%). PK1330 was found promising for selection, as it had desirable vegetative characters, including smaller petiole cross section (27.15 cm2), short rachis length (4.83 m), short palm height (1.85 m), and the lowest leaf number (164.6), as these vegetative characters are prerequisites for selecting palms for high density planting and high yield per hectare. The genetic variability among the progenies was found to be high, indicating ample scope for further breeding, followed by selection.